Isolation and molecular characterization of thermophilic coprophilous fungus malbranchea cinnamomea GSMBKU from goat dung - Ajmera, Shanthipriya; Rao, V. Koteswara; Ranipadmini, V.; Merugu, Ramchander; Girisham, Sivadevuni (Journal of Pure and Applied Microbiology, 2019)
Thermophilic fungi, found in the varied habitats are valuable sources for potential enzymes and other biochemical metabolites throwing challenges to the mycologists. A study of such fungi will not only enables the biochemists, microbiologists, and the biotechnologists to understand the basic molecular process but also search for novel genes, gene products and reactions. In this study, Malbranchea cinnamomea was isolated from goat dung and characterized based on its morphological and physiological characters, and later confirmed molecularly.